PENGETAHUAN SIKAP, DAN PERILAKU HIDUP BERSIH DAN SEHAT PADA MASYARAKAT DI DESA TARUMJAYA KERTASARI : (Analisis deskriptif PHBS Pada Masyarakat Bantaran Sungai Citarum) - ikhsan fuady; Ditha Prasanti; Rachmaniar (JURNAL TEKNOSAINS KODEPENA, 2021)
The purpose of this study is to describe the level of knowledge, attitudes and behavior in behaving in a healthy lifestyle. This research method is quantitative with a survey approach. This research was conducted in February 2018-July 2018, in the Upper Citarum River, Tarumjaya Village, Bandung Regency. This study analyzes the variables of knowledge, attitudes and behavior of PHBS with descriptive statistics. The results showed that the people's knowledge in Tarumjaya village was very good for all PHBS indikators. The highest indikator is childbirth in a health facility. The people of Tarumjaya Village have an attitude about a clean and healthy lifestyle in the high and medium categories. Most people have a good attitude in the dimension of childbirth assisted by health workers. Although the community's knowledge and attitudes regarding PHBS are quite good, in terms of community behavior in implementing PHBS, it still needs to be improved. As many as 69 percent have applied the medium and high category PHBS, but there are still 31 percent of the community who apply the PHBS in the low category.